Reduced humoral response 3 months following BNT162b2 vaccination in SARS-CoV-2 uninfected residents of long-term care facilities. (20th May 2022) - Trigueros, Macedonia; Pradenas, Edwards; Palacín, Dolors; Muñoz-López, Francisco; Ávila-Nieto, Carlos; Trinité, Benjamin; Bonet-Simó, Josep Maria; Isnard, Mar; Moreno, Nemesio; Marfil, Silvia; Rovirosa, Carla; Puig, Teresa; et al.
Abstract: Background: SARS-CoV-2 vaccination is the most effective strategy to protect older residents of long-term care facilities (LTCF) against severe COVID-19, but primary vaccine responses are less effective in older adults. Here, we characterised the humoral responses of institutionalised seniors 3 months after they had received the mRNA/BNT162b2 vaccine. Methods: plasma levels of SARS-CoV-2-specific total IgG, IgM and IgA antibodies were measured before and 3 months after vaccination in older residents of LTCF. Neutralisation capacity was assessed in a pseudovirus neutralisation assay against the original WH1 and later B.1.617.2/Delta variants. A group of younger adults was used as a reference group. Results: three months after vaccination, uninfected older adults presented reduced SARS-CoV-2-specific IgG levels and a significantly lower neutralisation capacity against the WH1 and Delta variants compared with vaccinated uninfected younger individuals. In contrast, COVID-19-recovered older adults showed significantly higher SARS-CoV-2-specific IgG levels after vaccination than their younger counterparts, whereas showing similar neutralisation activity against the WH1 virus and an increased neutralisation capacity against the Delta variant. Although, similarly to younger individuals, previously infected older adults elicit potent cross-reactive immune responses, higher quantities of SARS-CoV-2-specific IgG antibodies are required to reach the same neutralisation levels. Conclusions: although hybrid immunity seems to be active in previously infected older adults 3 months after mRNA/BNT162b2 vaccination, humoral immune responses are diminished in COVID-19 uninfected but vaccinated older residents of LTCF. These results suggest that a vaccine booster dose should be prioritised for this particularly vulnerable population.